Emergence of a novel PRRSV-1 strain in mainland China: A recombinant strain derived from the two commercial modified live viruses Amervac and DV - Sun, Qi; Xu, Hu; Li, Chao; Gong, Bangjun; Li, Zhen; Tian, Zhi-Jun; Zhang, Hongliang (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) is one of the main pathogens causing porcine reproductive and respiratory syndrome (PRRS). In recent years, the rate of PRRSV-1 detection in China has gradually increased, and the PRRSV-1 strains reported in China belong to subtype I (Global; Clade A-L). In the present study, a novel PRRSV-1 strain, TZJ2134, was found during epidemiological surveillance of PRRSV-1 in Shandong Province in China. We obtained two fragments of the TZJ2134 genome: TZJ2134-L12 (located at nt 1672-nt 2112 in the partial Nsp2 gene) and TZJ2134-(A+B) (located at nt 7463-nt 11272 in the partial Nsp9, complete Nsp10 and partial Nsp11 genes). Phylogenetic and recombination analyses based on the two sequences showed that TZJ2134 is a recombinant strain derived from two commercial PRRSV-1 modified live vaccine (MLV) strains (the Amervac vaccine and DV vaccine strains) that formed a new recombinant subgroup of DV+Amervac-like isolates with other strains. However, PRRSV-1 MLV is not currently allowed for use in China. This study is the first to detected recombinant PRRSV-1 MLV strain in China and provides new data for the epidemiological study of PRRSV-1 in China. The existence of the TZJ2134 strain is a reminder that the swine surveillance at the Chinese customs should be strengthened.